Sheep in the Vineyard: Suitability of Different Breeds and Potential Breeding Objectives - Lucas Conrad; Jakob Hörl; Maverick Henke; Rainer Luick; Nicolas Schoof (Animals, 2022)
Protecting a breed of sheep is simple when there is demand for its breed traits, but new market options are often hard to find. In general, grazing sheep are able to take over some viticultural work. Here, we address a new and promising integrated crop-livestock system that involves the integration of sheep in the vineyard during the growing season. Using sheep in a vineyard entails opportunities but also risks, such as the current lack of information, specifically in relation to breed traits. In our survey, we evaluated 26 breeds for their suitability for grazing as long as possible in Central European vineyards during the growing season. First, the breed traits required were identified. Then, 94 flock book breeders were interviewed about specific breed traits. The height of a sheep’s muzzle is particularly important for assessing the suitability of a breed, as it defines the potential impact on the foliage area during the growing season. To determine the height of the muzzle, 179 flock book animals were measured. We found that the most important breeding objective for a new breed of sheep is the inability to stand on two legs. Adult animals of the breed Shropshire, and among these especially the shorter-legged Danish type, and Southdown, show a widespread inability to stand on two legs. Ouessant sheep are able to do so, yet are suitable with some limitations. Due to their extraordinarily small size, their reach is limited, as is their grazing performance. Thus, three of the 26 breeds studied here seem suitable for use in the most widespread vine training systems of Central Europe during the growing season. Targeted breeding could further improve the suitability of sheep for viticulture. Our findings could help to protect breeds and breed traits.